The effectiveness of the implementation of the rights of women assisted citizens in realizing the purpose of Penitentiary in Penitentiary Class II A Rantauprapat - Iskandar Muda Sipayung (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This article tries to explain the rights of protection for people in detention centers. Many laws are made by the state. But practically, authorities in detention centers focus on the obligations and responsibilities of detainees rather than on their rights. So, this research group found some findings at its research site in Rutan, about unfair treatment, discrimination, rights violations, and other mistreatment.